A global burden of gastric cancer: the major impact of China. (3rd July 2017) - Nie, Yongzhan; Wu, Kaichun; Yu, Jun; Liang, Qiaoyi; Cai, Xiqiang; Shang, Yulong; Zhou, Jinfeng; Pan, Kaifeng; Sun, Liping; Fang, Jingyuan; Yuan, Yuan; You, Weicheng; et al.
ABSTRACT: Introduction : Gastric cancer (GC) is a highly aggressive cancer and a major cause of cancer-related deaths worldwide. Approximately half of the world's GC cases and deaths occur in china. GC presents challenges in early diagnosis and effective therapy due to a lack of understanding of the underlying molecular biology. The primary goals of this review are to outline current GC research in china and describe future trends in this field. Areas covered : This review mainly focuses on a series of GC-related advances China has achieved. Considerable progress has been made in understanding the role of H. pylori in GC by a series of population-based studies in well-established high-risk areas; A few germline and somatic alterations have been identified by 'omics' studies; Studies on the mechanisms of malignant phenotypes have helped us to form an in-depth understanding of GC and advance drug discovery. Moreover, identification of potential biomarkers and targeted therapies have facilitated the diagnosis and treatment of GC. However, many challenges remain. Expert commentary : To combat GC, sufficient funding is important. More attention should be paid on early diagnosis and the discovery of novel efficient biomarkers and the development of biomarker-based or targeted therapeutics in GC.